The LIFEwithIBD Intervention: Study Protocol for a Randomized Controlled Trial of a Face-to-Face Acceptance and Commitment Therapy and Compassion-Based Intervention Tailored to People With Inflammatory Bowel Disease - Trindade, Inês A.; Pereira, Joana; Galhardo, Ana; Ferreira, Nuno B.; Lucena-Santos, Paola; Carvalho, Sérgio A.; Oliveira, Sara; Skvarc, David; Rocha, Bárbara S.; Portela, Francisco; Ferreira, Cláudia (Frontiers in Psychiatry, 2021)
Background: There is ample evidence of the high mental health burden caused by Inflammatory Bowel Disease (IBD). Several constructs such as experiential avoidance, cognitive fusion, shame, and self-criticism have recently emerged as potential intervention targets to improve mental health in IBD. Psychotherapeutic models such as Acceptance and Commitment Therapy and compassion-based interventions are known to target these constructs. In this protocol, we aim to describe a two-arm Randomized Controlled Trial (RCT) testing the efficacy of an ACT and compassion-focused intervention named Living with Intention, Fullness, and Engagement with Inflammatory Bowel Disease (LIFEwithIBD) intervention + Treatment As Usual (TAU) vs TAU in improving psychological distress, quality of life, work and social functioning, IBD symptom perception, illness-related shame, psychological flexibility, self-compassion, disease activity, inflammation biomarkers, and gut microbiota diversity. Methods: This trial is registered at ClinicalTrials.gov (Identifier: NCT03840707, date assigned 13/02/2019). The LIFEwithIBD intervention is an adaptation to the IBD population of the Mind programme for people with cancer, an acceptance, mindfulness, and compassion-based intervention designed to be delivered in a group format. The LIFEwithIBD intervention’s structure and topics are presented in this protocol. Participants were recruited at the Gastroenterology Service of the Coimbra University Hospital between June and September 2019. Of the 355 patients screened, 61 participants were selected, randomly assigned to one of two conditions (experimental group [LIFEwithIBD + TAU] or control group [TAU]) and completed the baseline assessment. Outcome measurement took place at baseline, post-intervention, 3- and 12-month follow-ups. Discussion: Results from this RCT will support future studies testing the LIFEwithIBD intervention or other acceptance and/or compassion-based interventions for IBD.